Manufacture of Particle Board Made from Durian Peel - Riska Riska; Adian Rindang; Rudi Hartono (Universitas Sumatera Utara, 2016)
Durian is a tropical plant from southeast Asia. Durian peel is household waste which has high cellulose that can be used as raw material for particle board. This study aims to determine the effect of concentration of isocyanate adhesive to the physical and mechanical properties of particle board as well as to determine the optimal level of adhesive in the manufacture of particle board made from durian peel (Durio Zibethinus Murr.). The study was conducted from March until July 2015. The research was conducted at the Workshop and the Laboratory Technology of Forest Products department of Forestry Faculty of Agriculture, University of North Sumatra. UPT Agricultural Mechanization of Agriculture Department of North Sumatra. Parameters measured were density, moisture content, thickness swelling, DSA, Modulus Of Rupture and Modulus Of Elasticity of particle board. The results showed that the value of physical and mechanical properties of particle board from leather durian not comply with the JIS A 5908- 2003 standard, except for the density and moisture content as well as the development of thick adhesive 2 hours at levels of 5% and 7%. Adhesive optimal levels in this study were 5% gluten content. Keywords : Durian Peel, Adhesives Isocyanates, Particle Board